Collaborative, child-led philosophical inquiry in Religious and Moral Education - Cameron, Ewan (British Journal of religious education, 2022)
Situated in the context of the Scottish Religious and Moral Education (RME) curriculum, this article considers the practice of Community of Philosophical Inquiry (CoPI) and how it supports the RME curriculum. Sharing extracts from children’s CoPI sessions, the article reflects on the ways in which ten and eleven year-old children discuss religious and theological ideas philosophically. The child-led, collaborative approach demonstrates that the children work together to create meaning. It is proposed that the RME curriculum, or the enactment of the curriculum, often misses opportunities for children to engage with philosophical ideas about religious and theological concepts, and that an explicitly dialogic, philosophical approach affords important opportunities to support children’s self-understanding in-relation with the world and others.